Analysis of the Benefits of SAP S/4 HANA Cloud IT/Is Investment in the Case of PT XYZ - Sintya, Ni Kadek; Estiyanti, Ni Made; Putra, I Gede Juliana Eka; Máté, Domicián (International Journal of Engineering and Management Sciences, 2024)
PT XYZ is one of the largest telecommunication companies in Indonesia. In 2020, PT XYZ implemented a digital transformation to increase its excellence by investing in industry telecommunication and information systems (IT/IS) enterprise resource planning software called SAP (System Application and Processing) S/4 HANA Cloud. The study aims to analyze the benefits of these IT investments made in PT XYZ. The results are carried out using the Comparative Analysis of Financial Statements followed by Business Value and Financial Feasibility Analysis and the Cost Benefit Analysis (CBA) method between 2018 and 2021. It can be revealed that the SAP S/4 Hana Cloud investment benefits the company’s operations, which are identified in the form of 5 sub-categories that fall into required categories based on Ranti’s Generic IT/IS Business Value.